Evaluation of Severity and Factors Contributing to Foot Lesions in Endangered Ozark Hellbenders, Cryptobranchus alleganiensis bishopi - Hardman, Rebecca H.; Irwin, Kelly J.; Sutton, William B.; Miller, Debra L. (Frontiers in Veterinary Science, 2020)
Arkansas populations of Ozark Hellbenders, Cryptobranchus alleganiensis bishopi have declined precipitously over the past few decades and are now limited to a single river. Biologists have also observed an increase of distal limb lesions with unidentified etiology and unknown role in morbidity and mortality of the species in this location. We documented lesions and collected associated individual size class data and pathogen samples in Ozark Hellbenders of Arkansas (n=73) from 2011 – 2014 with the following two objectives: 1) document spatiotemporal patterns and severity of lesions present in this last remaining Arkansas Ozark Hellbender population, and 2) determine if host factors and infection status are associated with lesion severity. A scoring system was created from 0-7 based on lesion observations. Linear mixed model regressions followed by AICc model evaluation were used to determine associations among infection status for amphibian pathogens Batrachochytrium dendrobatidis (Bd) and Ranavirus as well as individual biometrics on lesion score. We discovered 93.2% of hellbenders had lesions characterized by digit swelling that often progressed towards toe-tip ulceration. In severe cases we observed digital necrosis progressing to digit loss. Any recaptured individuals had the same or worse lesion score from previous captures. The top predictive model for lesion severity included individual mass and Bd infection status with a significant, positive association of Bd with increased lesion severity (β= 0.87 ± 0.39 S.E., C.I.: 0.11, 1.63). Our findings highlight a widespread and progressive disease that is an important factor to consider for the future of Ozark Hellbenders. This syndrome is presumptively multifactorial, and future studies will benefit from investigating several factors of host, infectious agents, and environment and their roles in disease manifestation for the purpose of developing effective, multi-faceted conservation strategies. A summary of potential etiologies and mechanisms is provided that may explain observed lesion distribution and that will be applicable to future disease and epidemiological investigations.